Study on the nutritional values and customer acceptance of Lansium domesticum & Nephelium lappaceum newly fermented natural fruit vinegars in Malaysia - Seri Intan Mokhtar; Faznira Zakaria; Mohammad Amizi Ayob; Siow, Woon Soon; Nurshahida. A.S; Zul Ariff Abdul Latiff (Asia Pacific Institute Of Advanced Research, 2016)
Every fruit season, the orchard farmers are facing fruit overloading leading towards fruit dumping. Nephelium lappaceum (local name: Rambutan) and Lansium domesticum (local name: Dokong) vinegars were produced by natural microbial fermentation to overcome the dumping problem. The Vinegars nutritional values and customer acceptance studies were conducted to compare against commercially available vinegars in Malaysia. Rambutan and Dokong vinegars nutritional value were shown to contain the same carbohydrate, protein and fat value with the apple cider vinegar and Attap seed (nipa) vinegars. Both vinegars contained two times higher Potassium, four times lower Sodium and eight times higher calcium compared to Apple Cider Vinegar. The survey method by using the structured questionnaire was used as a tool for collecting data and information. A total of 177 respondents by using stratiﬁed random sampling ﬁlled up the questionnaire in selected location in Kuala Lumpur and Kelantan to obtain the result on acceptance of this natural fruit vinegar product. The result indicated most of the customers preferred the vinegar from fruit compared to Attap seed (nipa) vinegar and artiﬁcial vinegar. In addition, Halal and nutrition value of the product are of concerned to the consumers.